2019
DOI: 10.1371/journal.pone.0223786
|View full text |Cite
|
Sign up to set email alerts
|

Maize leaves drought-responsive genes revealed by comparative transcriptome of two cultivars during the filling stage

Abstract: Like other important cereal crop in modern agricultural production, maize is also threatened by drought. And the drought stress during maize filling stage will directly affect the quality (protein or oil concentration) and also the weight of grain. Therefore, different from previous studies focusing on inbred lines and pot experiment at seedling stage, current study selected filling stage of the adult plant and planting maize in the experimental field. Two hybrids cultivars with different drought tolerant were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…We observed a large decrease in abundance of an O-glycosyl hydrolase (GH) domain-containing protein Solyc05g050130. The GH protein family hydrolyzes carbohydrates from other molecules, and have been linked to many biological processes [ 77 ] but are most likely involved in cell wall modification [ 78 , 79 ]. Another substantially decreased phloem sap protein, the xyloglucan endotransglucosylase (XTH, Solyc03g093130), is also likely involved in cell wall development, and similar XTH proteins are known to be involved in vascular cell wall expansion in poplar [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…We observed a large decrease in abundance of an O-glycosyl hydrolase (GH) domain-containing protein Solyc05g050130. The GH protein family hydrolyzes carbohydrates from other molecules, and have been linked to many biological processes [ 77 ] but are most likely involved in cell wall modification [ 78 , 79 ]. Another substantially decreased phloem sap protein, the xyloglucan endotransglucosylase (XTH, Solyc03g093130), is also likely involved in cell wall development, and similar XTH proteins are known to be involved in vascular cell wall expansion in poplar [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Seeds of the two hybrids were provided by the North China Key Laboratory for Crop Germplasm Resources of Education Ministry, Hebei Agricultural University, China. The detailed criteria on our selection of these hybrids are described in our recent study [34].…”
Section: Plant Materials and Drought Stress Treatmentmentioning
confidence: 99%
“…Two maize hybrids with dissimilar drought tolerance (drought-tolerant NongDan 476 and drought-sensitive ZhongXin 978) were used in this study [26]. The materials were provided by the laboratory (North China Key Laboratory for Crop Germplasm Resources of Education Ministry, Hebei Agricultural University, Baoding, China).…”
Section: Plant Materials and Treatmentmentioning
confidence: 99%
“…For instance, Guo et al [25] examined the transcriptomic changes induced by drought and salt stress in 8-week-old seedlings of Picea wilsonii via RNA-seq analysis. Previously, we conducted comparative RNA-seq transcriptome studies [26][27][28] and identified several candidate genes and metabolic pathways for drought tolerance in maize, including secondary metabolite biosynthesis related enzymes, such as probable Omethlytransfarase 2 (OMT2; Zm00001d019613) [28]; transcription factors (TF) such as MYBs, NAC and WRKYs; detoxification and stress responsive proteins including aquaporin PIP2-4 (Zm00001d017288), HSPs and GSTs [26][27][28]. However, transcriptome analysis of drought tolerance mechanisms is limited because mRNA translation levels are not always related to the corresponding protein levels and proteins are the direct bearers of biological function [29,30].…”
Section: Introductionmentioning
confidence: 99%